The Implementation of Learning to Write Fantasy Story Texts Using the Invention Model in Junior High School - Yulianti, Yolani; Rati, Safrina; Juwanda, Juwanda; Nurzaman, Bela (Jurnal Edusci, 2025)
Background. Academic writing depends not only on individual skills, but also on habits and strategies that support productivity. In conducting research, establish a structured work pattern, utilize time effectively, and create an environment that fosters consistency in writing. Aims. To explore the experience of language teachers: how the discovery model is used in practice and its impact on the interaction between teacher and student. Methods. The research method used in this study is qualitative descriptive. Data source of Indonesian teachers in junior high school, totalling two people who have used the invention model in learning to write fantasy texts. Participants were selected based on the criteria of active involvement in using the discovery model, as well as relevant teaching experience. Result. Teachers hope for the development of a more flexible, intuitive, and accessible learning model. The support needed includes ongoing training, the provision of digital devices in schools, and a curriculum that is adaptive to the use of discovery models. Collaboration between the government and schools is needed to realize more effective and equitable learning. Conclusion. The use of educational technology in language learning, particularly in writing fantasy texts in junior high school, has a significant positive impact on both the learning process and the experience of students and teachers. Implementation. The discovery model in education can encourage students to improve their critical thinking skills, creativity, and engagement in the learning process.